Rehabilitation augments hematoma clearance and attenuates oxidative injury and ion dyshomeostasis after brain hemorrhage - Williamson, M.; Dietrich, K.; Hackett, Mark; Caine, S.; Nadeau, C.; Aziz, J.; Nichol, H.; Paterson, P.; Colbourne, F. (Lippincott Williams & Wilkins, 2017)
© 2016 American Heart Association, Inc.Background and Purpose - We assessed the elemental and biochemical effects of rehabilitation after intracerebral hemorrhage, with emphasis on iron-mediated oxidative stress, using a novel multimodal biospectroscopic imaging approach. Methods - Collagenase-induced striatal hemorrhage was produced in rats that were randomized to enriched rehabilitation or control intervention starting on day 7. Animals were euthanized on day 14 or 21, a period of ongoing cell death. We used biospectroscopic imaging techniques to precisely determine elemental and molecular changes on day 14. Hemoglobin content was assessed with resonance Raman spectroscopy. X-ray fluorescence imaging mapped iron, chlorine, potassium, calcium, and zinc. Protein aggregation, a marker of oxidative stress, and the distribution of other macromolecules were assessed with Fourier transform infrared imaging. A second study estimated hematoma volume with a spectrophotometric assay at 21 days. Results - In the first experiment, rehabilitation reduced hematoma hemoglobin content (P=0.004) and the amount of peri-hematoma iron (P<0.001). Oxidative damage was highly localized at the hematoma/peri-hematoma border and was decreased by rehabilitation (P=0.004). Lipid content in the peri-hematoma zone was increased by rehabilitation (P=0.016). Rehabilitation reduced the size of calcium deposits (P=0.040) and attenuated persistent dyshomeostasis of Cl - (P<0.001) but not K + (P=0.060). The second study confirmed that rehabilitation decreased hematoma volume (P=0.024). Conclusions - Rehabilitation accelerated clearance of toxic blood components and decreased chronic oxidative stress. As well, rehabilitation attenuated persistent ion dyshomeostasis. These novel effects may underlie rehabilitation-induced neuroprotection and improved recovery of function. Pharmacotherapies targeting these mechanisms may further improve outcome.